Performance evaluation of different troposphere delay models and mapping functions - El-Mowafy, Ahmed; Tuka, A. (Elsevier Ltd., 2013)
Tropospheric delay is a major error source in positioning by Global Navigation Satellite Systems (GNSSs). System users often apply one of the available troposphere models without giving sufficient background on their performance. In this study, the performance of different known hydrostatic and wet troposphere delay models and mapping functions are internally and externally compared and analysed at selected sites around the globe. International GNSS Service (IGS) products were used as a reference. The best performing models are presented. Results showed that small discrepancies are present between different models. All models perform significantly better at the mid-latitudes than at the Equator.